2018
DOI: 10.7717/peerj.4623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fertilizations on soil bacteria and fungi communities in a degraded arid steppe revealed by high through-put sequencing

Abstract: BackgroundFertilization as one of the measures in restoring degraded soil qualities has been introduced on arid steppes in recent decades. However, the fertilization use efficiency on arid steppes varies greatly between steppe types and years, enhancing uncertainties and risks in introducing fertilizations on such natural system to restore degraded steppes.MethodsThe experiment was a completely randomized design with five fertilization treatments, 0 (Control), 60 kg P ha−1 (P), 100 kg N ha−1 (N), 100 kg N ha−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 80 publications
2
14
0
Order By: Relevance
“…Previous studies have shown that the diversity and composition of bacterial communities associated with plant roots and rhizosphere soil are affected by a series of biotic and abiotic factors, such as fertility, pH and soil moisture (Shen et al, 2013;Zhang et al, 2014b;Yao et al, 2018). These factors normally lead to changes in the physical and chemical properties of rhizosphere soil and soil nutrient levels, which are closely related to the diversity of rhizosphere soil and root bacteria (Bulgarelli et al, 2012;Fan et al, 2017;Francioli et al, 2017).…”
Section: Relationships Between Bacteria Community and Environmental Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the diversity and composition of bacterial communities associated with plant roots and rhizosphere soil are affected by a series of biotic and abiotic factors, such as fertility, pH and soil moisture (Shen et al, 2013;Zhang et al, 2014b;Yao et al, 2018). These factors normally lead to changes in the physical and chemical properties of rhizosphere soil and soil nutrient levels, which are closely related to the diversity of rhizosphere soil and root bacteria (Bulgarelli et al, 2012;Fan et al, 2017;Francioli et al, 2017).…”
Section: Relationships Between Bacteria Community and Environmental Fmentioning
confidence: 99%
“…The composition and diversity of bacterial communities in soil and roots are considered as indicators reflecting plant biomass, mineral resources acquisition and biological processes, which are inevitably affected by host plant and environmental factors, including pH (Shen et al, 2013), nutrient availability (Meyer et al, 2013), soil moisture (Zhang et al, 2014b), and fertility (Yao et al, 2018). These factors alter rhizosphere soil microbial communities by changing soil physical and chemical properties, nutrient cycling and phytohormones production (Zhang et al, 2014b;Francioli et al, 2017;Zhalnina et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the present study we found that AMF community diversity was signi cantly positively correlated with soil pH, potentially due to unique local environmental factors. Some studies have shown that the tolerance of different AMF species to soil pH values varies greatly [50,51], and the diversity and community composition of AMF species in soils with different pH values were signi cantly different [52][53][54]. The soil pH range in the present study was from 7.80-8.81, with only certain Glomus and Diversispora AMF species being able to survive in this pH range.…”
Section: Discussionmentioning
confidence: 46%
“…In contrast, in the present study, we found that AMF community diversity was signi cantly positively correlated with soil pH, potentially due to unique local environmental factors. Some studies have shown that the tolerance of different AMF species to soil pH varies greatly [50,51], and that the diversity and community composition of AMF species in soils with different pH values were signi cantly different [52][53][54]. The soil pH range in the present study was from 7.80-8.81, with only certain Glomus and Diversispora AMF species being able to survive in this pH range.…”
Section: Discussionmentioning
confidence: 47%